Analysis of performance determinants in open water swimmers and triathletes - López-Belmonte, Ó (2024)
Open water (OW) swimming and triathlon are rapidly growing endurance sports, both characterized by the unique challenges of swimming in natural OW environments. However, research into the determinants of performance in these sports remains underexplored. Therefore, the main aim of this thesis is to deepen the understanding of the performance determinants of elite open water swimmers and triathletes. To explore these determinants further, three studies were conducted with elite open water swimmers: i) analysis of the 3000 m swimming pacing strategy and its variability in performance; ii) 7x400 m incremental test to determine lactate threshold and examine its relationship with performance; iii) 7x400 m incremental tests to assess longitudinal changes between seasons. On the other hand, to increase knowledge of the swimming leg of triathlon, three studies were conducted with elite triathletes: i) 1500 m swimming test in pool; ii) 1500 m swimming test in OW; iii) comparison of 1500 m swimming tests between OW and pool conditions. All of these studies focused on physiological and biomechanical factors. The results of this thesis evidenced that OW swimmers: i) adopted a parabolic pacing strategy, showing variations in turn performance and stroke parameters; ii) high swimming speeds at lactate threshold, associated with improved competitive performance; iii) there were no seasonal changes in performance or physiological factors, but there were biomechanical adaptations between tests. Regarding triathletes: i) metabolic efficiency and technical skill determined pool swimming performance; ii) OW swimming caused variations in biomechanical factors, with efficiency being the performance determinant; iii) OW conditions impaired kinematics and efficiency compared to pool swimming, but the physiological demands were similar in both environments. In conclusion, the findings of this thesis provide a comprehensive insight into the training and competitive performance of both OW swimmers and triathletes. The holistic approach to monitoring training or assessing different swimming conditions offers relevant information for swimmers, triathletes and coaches.